T Helper 2-Associated Immunity in the Pathogenesis of Systemic Lupus Erythematosus - Ko, Haeun; Kim, Chan Johng; Im, Sin-Hyeog (Frontiers in Immunology, 2022)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that mainly affects women in their reproductive years. A complex interaction of environmental and genetic factors leads to the disruption of immune tolerance towards self, causing overt immune activation and production of autoantibodies that attack multiple organs. Kidney damage, termed lupus nephritis, is the leading cause of SLE-related morbidity and mortality. Autoantibodies are central to propagating lupus nephritis through forming immune complexes and triggering complements. Immunoglobulin G (IgG) potently activates complement; therefore, autoantibodies were mainly considered to be of the IgG isotype. However, studies revealed that over 50% of patients produce autoantibodies of the IgE isotype. IgE autoantibodies actively participate in disease pathogenesis as omalizumab treatment, a humanized anti-IgE monoclonal antibody, improved disease severity in an SLE clinical trial. IgE is a hallmark of T helper 2-associated immunity. Thus, T helper 2-associated immunity seems to play a pathogenic role in a subset of SLE patients. This review summarizes human and animal studies that illustrate type 2 immune responses involved during the pathology of SLE.